2010
DOI: 10.1175/2009jcli2979.1
|View full text |Cite
|
Sign up to set email alerts
|

Coherence between the Great Salt Lake Level and the Pacific Quasi-Decadal Oscillation

Abstract: The lake level elevation of the Great Salt Lake (GSL), a large closed basin lake in the arid western United States, is characterized by a pronounced quasi-decadal oscillation (QDO). The variation of the GSL elevation is very coherent with the QDO of sea surface temperature anomalies in the tropical central Pacific (also known as the Pacific QDO). However, such coherence denies any direct association between the precipitation in the GSL watershed and the Pacific QDO because, in a given frequency, the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…It is also noteworthy that Gillies et al's GSL forecast, that began in 2008 and lead up to 2015 (delineated and indicated by arrow in Fig. 1b increase in the GSL level had yet to occur; this circumstance supported the connection proposed in Wang et al (2010), i.e. that the so-called Pacific Quasi-Decadal Oscillation (QDO) figured as a dominant climate phenomenon in the Intermountain West and was a strong contemporary driver of the region's hydroclimate.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…It is also noteworthy that Gillies et al's GSL forecast, that began in 2008 and lead up to 2015 (delineated and indicated by arrow in Fig. 1b increase in the GSL level had yet to occur; this circumstance supported the connection proposed in Wang et al (2010), i.e. that the so-called Pacific Quasi-Decadal Oscillation (QDO) figured as a dominant climate phenomenon in the Intermountain West and was a strong contemporary driver of the region's hydroclimate.…”
Section: Introductionsupporting
confidence: 58%
“…Due to its large surface area that is contained within a closed basin, fluctuations in the GSL level duly reflect the hydroclimate conditions of the region: i.e. the highest water mark lags after the peak in the precipitation regime (of the region's prominent wet-dry cycle) while the lowest water mark occurs after the onset of the low point in the precipitation regime (Wang et al, 2010), a condition oftentimes created by persistent drought. The lake level fluctuation (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, only an indirect link or a coincidence can explain such an association between the Pacific QDO and the precipitation source of the GSL. Wang et al (2010a) investigated this phenomenon and found that the quasi-decadal variation in the IMW precipitation consistently lags the Pacific QDO by a quarter-phase, i.e. 3 years after the peak of the warm-phase Pacific QDO occurs, an anomalous trough develops over the Gulf of Alaska and enhances the IMW precipitation (similar to the situation in Fig.…”
Section: B Quasi-decadal Cyclementioning
confidence: 77%